416PMultidisciplinary management of sarcomas of the head and neck: An institutional experience. (24th November 2019) - Jain, K; Kumar, V; Chaturvedi, A; Misra, S; Gupta, S; Akhtar, N; Garg, S; Lakshmanan, M
Abstract: Background: Head and neck cancer is one of the most common malignancies in India, with the highest incidence worldwide. Our aim was to study head and neck sarcomas- tumor types, their treatment strategies, recurrence patterns and survival in patients treated in a tertiary centre in the densely populated Northern India. Methods: This is a retrospective study of a prospectively maintained database. Patients treated between January 2011- June 2016 at the centre were included. Surgical treatment was wide excision (aim was to get disease free margins within the restrictions of the region). Chemotherapy was mainly doxorubicin-based with drugs like cisplatin, ifosfamide, etoposide, vincristine and cyclophosfamide added as per the histology. Radiotherapy was given as part of the curative treatment in Ewing's sarcoma. Adjuvant radiation therapy was given in close/involved margins or locally advanced disease in other histologies. Patients with distant or locally advanced disease underwent multimodal management. Results: The study included 29 cases. Histologies were varied, with the most common type being osteosarcoma, followed by chondrosarcoma. Ewing's sarcoma, pleomorphic sarcoma and spindle cell sarcoma were the other common types. Most common site of involvement was mandible. Surgery was done in 68.9% (n = 20). High grade disease was seen in 22 patients (75.9%). Margins were clear in 17 patients (80.9%); close margins were documented in 4 patients (19%). Locoregional and distant recurrences occurred in 15% (n = 3) & 10% (n = 2), respectively. Factors affecting the risk of recurrence are high grade, close margins and locally advanced disease. However there is no influence of size, grade or margin status on survival. Median survival was 33 months. The 3 year disease free survival was 52% (95% CI- 0.44-0.83). Conclusions: Head and neck sarcoma is a rare heterogeneous group in one of the commonest sites of malignancy in India. Apart from appropriate identification of the cases, the better chance of survival is provided by an expert unit with multidisciplinary management, and chance of surgical salvage in case of recurrence. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.